Omecamtiv mecarbil does not prolong QTc intervals at therapeutic concentrations. Issue 1 (16th July 2021) - Trivedi, Ashit; Hsu, Cheng‐Pang; Jafarinasabian, Pegah; Terminello, Bianca; Zhang, Hanze; Flach, Stephen; Israel, Samuel; Brooks, Ashley; Xue, Hongqi; Darpo, Borje; Abbasi, Siddique; Dutta, Sandeep; et al.
Abstract : Aims: Omecamtiv mecarbil (OM) is a novel selective cardiac myosin activator under investigation for the treatment of heart failure. This study aimed to evaluate the effect of therapeutic concentrations of OM on electrocardiogram (ECG) parameters and exclude a clinically concerning effect on the rate‐corrected QT (QTc) interval. Methods: In part A, 70 healthy subjects received a 25 mg oral dose of OM, and pharmacokinetics were assessed. Only subjects with maximum observed plasma concentration ≤ 350 ng/mL ( n = 60) were randomized into part B, where they received a single oral dose of placebo, 50 mg OM and 400 mg moxifloxacin in a 3‐period, 3‐treatment, 6‐sequence crossover study with continuous ECG collection. Results: After a 50‐mg dose of OM, mean placebo‐corrected change from baseline QTcF (∆∆QTcF; Fridericia correction) ranged from −6.7 ms at 1 hour postdose to −0.8 ms at 4 hours postdose. The highest upper bound of the 1‐sided 95% confidence interval (CI) was 0.7 ms (4 h postdose). Moxifloxacin resulted in a clear increase in mean ∆∆QTcF, with a peak value of 13.1 ms (90% CI: 11.71–14.57) at 3 hours; lower bound of the 1‐sided 95% CI was > 5 ms at all of the 3 prespecified time points. Based on a concentration–QTc analysis, an effect on ∆∆QTcF exceeding 10 ms can be excluded up to OM plasma concentrations of 800 ng/mL. There were no serious or treatment‐emergent adverse events leading to discontinuation from the study. Conclusion: OM does not have a clinically relevant effect on the studied ECG parameters. Abstract : After a 50‐mg dose of OM, ∆∆QTcF ranged from −6.7 ms at 1 hour postdose to −0.8 ms at 4 hours postdose. Based on a concentration‐QTc analysis, an effect on ∆∆QTcF exceeding 10 ms can be excluded up to OM plasma concentrations of 800 ng/mL.